Improved Photodynamic Efficacy of Zn(II) Phthalocyanines via Glycerol Substitution - Chin, Yunni (Public Library of Science, 2014)
Phthalocyanines are excellent photosensitizers for photodynamic therapy as they have strong absorbance in the near infra-red region which is most relevant for in vivo activation in deeper tissular regions. However, most phthalocyanines present two major challenges, ie, a strong tendency to aggregate and low water-solubility, limiting their effective usage clinically. In the present study, we evaluated the potential enhancement capability of glycerol substitution on the photodynamic properties of zinc (II) phthalocyanines (ZnPc). Three glycerol substituted ZnPc, 1–3, (tetra peripherally, tetra non-peripherally and mono iodinated tri non-peripherally respectively) were evaluated in terms of their spectroscopic properties, rate of singlet oxygen generation, partition coefficient (log P), intracellular uptake, photo-induced cytotoxicity and vascular occlusion efficiency. Tetrasulfonated ZnPc (ZnPcS(4)) was included as a reference compound. Here, we showed that 1–3 exhibited 10–100 nm red-shifted absorption peaks with higher molar absorptivity, and at least two-fold greater singlet oxygen generation rates compared to ZnPcS(4). Meanwhile, phthalocyanines 1 and 2 showed more hydrophilic log P values than 3 consistent with the number of glycerol attachments but 3 was most readily taken up by cells compared to the rest. Both phthalocyanines 2 and 3 exhibited potent phototoxicity against MCF-7, HCT-116 and HSC-2 cancer cell-lines with IC(50) ranging 2.8–3.2 µM and 0.04–0.06 µM respectively, while 1 and ZnPcS(4) (up to 100 µM) failed to yield determinable IC(50) values. In terms of vascular occlusion efficiency, phthalocyanine 3 showed better effects than 2 by causing total occlusion of vessels with diameter <70 µm of the chorioallantoic membrane. Meanwhile, no detectable vascular occlusion was observed for ZnPcS(4) with treatment under similar experimental conditions. These findings provide evidence that glycerol substitution, in particular in structures 2 and 3, is able to improve the photodynamic properties of ZnPc.